Reasons they serve: older adults' motivations to volunteer in faith-based organizations - Jensen, Brad M., author; Makela, Carole J., advisor; Gloeckner, Gene W., committee member; Shelton, Paul M., committee member; Hoxmeier, John A., committee member (Colorado State University. Libraries, 2016)
This quantitative study analyzed older adults’ motivations to volunteer in faith-based organizations. Volunteerism among older adults is critical for faith-based organizations and is equally important for older adults themselves. Volunteering provides the needed workforce for faith-based organizations to accomplish their mission and provides meaningful service to older adults who are volunteering. This study explored which motivations to volunteer were most important to older adults in faith-based organizations and studied the relationships between motivation to volunteer and participants’ gender, present volunteer status, age, and work status. The study used a modified edition of a survey developed by Clary and associates called the Volunteer Functions Inventory (VFI), which identifies six motivations to volunteer (values, understanding, enhancement, social, protective, and career). The survey contains five items for each motivation. An additional five items were added to the original VFI’s 30 items to measure the motivation of continuity (continuing to use professional knowledge and skills). The first section of the survey was the modified VFI and the second part asked for demographic data. There were 395 participants from five different churches in Colorado and Iowa. Respondents were adults 50 years and older. Sixty-one percent were female and 54% of the participants were presently volunteering in or through their church 8 hours or more a month. Eighty-two percent of the participants were between the ages of 50 and 70. Forty-two percent of the participants were not working. Of those working, 66% were working full-time. The data were analyzed using ANOVA and post hoc statistics to determine differences in motivations to volunteer based on gender, volunteer status, age, and work status. The findings suggest the values and understanding motivations were the most important motivations for older adults to volunteer in faith-based organizations and the career motivation was the least important. There were small differences between motivations to volunteer based on gender, volunteer status, age, and work status. For example, the social motivation was more important to men than women, especially men 70 years and older. The implication for faith-based organizations and their volunteer managers is the need to communicate how volunteer activity provides an opportunity to express personal values and increase understanding. Additionally, faith-based organizations need to create specific volunteer management strategies based on the differences in motivation to volunteer by age, gender, volunteer status, and work status.